2023
DOI: 10.1177/09544062231206950
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the mounting surface error on the deformation of the guideway

Luqi Song,
Qiang Zhang,
Xuesen Zhao
et al.

Abstract: The guideway is deformed due to the clamp force of the bolt and the manufacturing error of the mounting surface. Deformation and manufacturing error constitute the guideway straightness error. In this paper, the pressure distribution of the bolt in the tightened state is simulated first, the relationship between the bolt clamp force and the tightening torque is calculated, and then the deformation of the guideway under different tightening torques is simulated. Finally, experiments are carried out on a guidewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Their findings revealed that thermal elevation can lead to significant deformations, further compounding surface errors, as highlighted by subsequent studies conducted by Li et al (2018) and Lei et al (2021). Furthermore, the structural integrity of hydrostatic guideway can be compromised by localized deformations resulting from screw preload, manifesting as contour errors on the oil film contact surface, which can be considered as assembly errors (Song et al, 2023).…”
Section: Introductionmentioning
confidence: 95%
“…Their findings revealed that thermal elevation can lead to significant deformations, further compounding surface errors, as highlighted by subsequent studies conducted by Li et al (2018) and Lei et al (2021). Furthermore, the structural integrity of hydrostatic guideway can be compromised by localized deformations resulting from screw preload, manifesting as contour errors on the oil film contact surface, which can be considered as assembly errors (Song et al, 2023).…”
Section: Introductionmentioning
confidence: 95%